EXPLORING DOCTORAL SUPERVISION IN LAW EDUCATION: PERSPECTIVES IN TEACHING AND PEDAGOGY (Malaysian Journal of Learning and Instruction, 2025)
Purpose - This paper explores the pedagogical practices employed in supervising law PhD students within law schools. The study adopts an auto-ethnographic approach to investigate the beliefs of both supervisors and students regarding teaching, learning, research and supervision. Methodology - An overarching auto-ethnographic method was used to examine the perspectives of students and supervisors on teaching, learning, research and supervision. Data collection spanned eight months and followed a multi-step process. The first set of data was obtained through a focus group comprising five supervisors from the Business and Law Faculty. The second set of data involved naturalistic observations of three supervisory meetings per supervisor and their respective students. The final set of data was collected through the observation of five student annual progression panel proceedings, focusing on the same five students whose supervisory sessions were previously observed. Findings - The observations revealed five distinct pedagogical approaches to teaching within the supervisory context. Additionally, participants’ beliefs were found to be interconnected, allowing for the identification of orientations. Participants aligned with a particular orientation exhibited a unique set of beliefs. It was noted that a supervisor’s choice of orientation influences the overall pedagogical approach adopted during supervision. Each orientation incorporated an element of teaching, highlighting the integral role of teaching within supervisory practices. Significance - The findings have significant implications for faculty professional development, particularly for staff involved in doctoral supervision. They provide insights into the dynamics of student learning during interactions between staff and students throughout the doctoral journey. These insights can inform future supervision training programmes, offering valuable guidance to novice supervisors and enhancing the overall doctoral supervision experience.